PERSONALIZED APPROACH IN THE THERAPY OF PCOS: MODERN OPPORTUNITIES AND CLINICAL EFFECTIVENESS - Agababyan , L.R.; Usmonkulova , Kh.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Polycystic ovary syndrome is a heterogeneous complex disorder characterized by oligoanovulation, hyperandrogenism and/or hyperandrogenemia, as well as polycystic morphological changes in the ovaries. Interest in PCOS encompasses several specific aspects, including reproductive, cosmetic, and medical ones.